HOW DOES SOCIAL IMPACT INFLUENCE CULTURAL ENTREPRENEURSHIP? AN EXPLORATORY CASE STUDY TO UNDERSTAND THE POTENTIAL OF THE 2030 AGENDA THROUGH DIGITAL TRANSFORMATION - Oppioli, Michele; Lanzalonga, Federico; Biancone, Paolo Pietro (Piccola Impresa / Small Business, 2025)
Purpose. This study examines the adoption of digital tools for data visualisation in evaluating the social impact within cultural and creative industries, focusing on their alignment with the Sustainable Development Goals. Design/methodology/approach. Through the adoption of an action-research framework, this study combines qualitative and quantitative approaches. It includes a single-case study rigorously analysed over 24 months, employing interviews and triangulation of data sources to thoroughly assess social impact metrics. Findings. The study presents a detailed phased framework for implementing effective social impact evaluation systems within the cultural and creative industries, guided by the Theory of Change. It demonstrates that digital tools for data visualisation, particularly Business Intelligence systems, enhance data collection and analysis, thereby facilitating improved decision-making and communication of social impact. Practical and Social Implications. The study underscores the practical implementation of a Business Intelligence-driven framework, proposing it as a best practice for cultural organisations aiming to demonstrate their social impact sustainably. This framework fosters cultural and creative industries aligning their activities with the Sustainable Development Goals by offering a clear methodology for measuring and reporting these impacts. Additionally, the significance of digital tools for data visualisation in enhancing the transparency and efficiency of social impact assessments in the cultural sector is highlighted. By presenting a model adoptable by other entities, the study proposes a pathway for enhancing societal outcomes through cultural activities, thereby expanding the potential for systemic change in the perception and valuation of cultural impacts. Originality of the study. This research provides original insights into the application of digital technologies for evaluating social impacts within cultural and creative industries. By integrating the Theory of Change with digital Business Intelligence tools, the study introduces a novel approach to operationalising Sustainable Development Goals in the cultural sector, thereby enhancing the precision and reliability of impact assessments.